Meningkatkan Prestasi Belajar Al-Qur’an-Hadis Melalui Metode Demonstrasi pada Siswa Madrasah Aliyah - Muhammad Iqbal; mohammad agus fatkhur rohman; sunyahni sunyahni; karmila sari; Tamrin Fatoni (https://ejournal.insuriponorogo.ac.id/, 2024)
This article aims to describe the results of a classroom action research on the learning process using demonstration method and how this method improves students’ learning achievement in Al-Qur'an-Hadith subject. The participants of this study were students of class XI. Data collection techniques used observation, learning outcomes tests and documentation. Data was analized qualitatively and quantitatively. The results of data analysis showed that demonstration method could trigger students' responses to better learning so that they become more active in the learning process. The results of data analysis indicate that the implementation of demonstration method could improve students’ achievement in Al-Quran-Hadith subject.